1980
DOI: 10.1042/bj1920673
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of l-tryptophan by isolated rat liver cells. Quantification of the relative importance of, and the effect of nutritional status on, the individual pathways of tryptophan metabolism

Abstract: 1. The metabolism of L-tryptophan by liver cells prepared from fed and 48 h-starved rats was studied. Methods are described, with the use of L-[ring-2-14C], L-[carboxy-'4C1-and L-[benzene-ring-U-'4C]-tryptophan, for the simultaneous determination of tryptophan 2,3-dioxygenase and kynureninase activities and of the oxidation of tryptophan to CO2 and non-aromatic intermediates of the kynurenine-glutarate pathway. 2. At physiological concentrations (0.1 mM), tryptophan was oxidized by tryptophan 2,3-dioxygenase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 43 publications
5
20
0
Order By: Relevance
“…The incubation conditions for determining fluxes through tryptophan 2,3 -dioxygenase and kynureninase and to non-aromatic products of the glutarate pathway in isolated liver cell preparations by using L-[ring-2-'4C]-, L-[carboxyl-'4C1-and L-[benzene-ring-U-'4C1-tryptophan respectively were identical with those described previously (Smith & Pogson, 1980b;Smith et al, 1980).…”
Section: Animals and Liver Cell Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The incubation conditions for determining fluxes through tryptophan 2,3 -dioxygenase and kynureninase and to non-aromatic products of the glutarate pathway in isolated liver cell preparations by using L-[ring-2-'4C]-, L-[carboxyl-'4C1-and L-[benzene-ring-U-'4C1-tryptophan respectively were identical with those described previously (Smith & Pogson, 1980b;Smith et al, 1980).…”
Section: Animals and Liver Cell Preparationmentioning
confidence: 99%
“…Pharmaceuticals, Alderley Park, Cheshire, U.K.). The sources of all other materials have been detailed earlier (Smith & Pogson, 1980b;Smith et al, 1980).…”
Section: Chemicalsmentioning
confidence: 99%
“…These factors permit the experimenter to incubate more than IOO samples at a time, because processing, subsequent to quenching with acid, merely consists of absorption of 14C0, with phenylethylamine, adsorption of aromatic compounds on to Norit GSX, brief centrifugation and removal of supernatant fractions for counting (e.g. Smith & Pogson, 1980;Dickson et al 1981;Smith et al 1981).…”
Section: Aromatic Amino Acid Metabolismmentioning
confidence: 99%
“…Additionally, the agent has been shown not to be a specific inhibitor, because it also inhibits other enzymes in the tryptophan oxidative pathway at concentrations that are likely to be encountered in vivo after administration to experimental animals (Bender, 1980;Smith & Pogson, 1981). In fact, in spite of the protective effect of carbidopa on the tryptophan-induced hypoglycaemia, it has been suggested that 5-HT is unlikely to mediate the hypoglycaemic response to tryptophan (Smith et al, 1980;Lloyd et al, 1982a,b). Therefore, the possibility that metabolites of 5-HTP other than 5-HT may contribute to the development of 5-HTP-induced hypoglycaemia cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%